Analysis Of The Influence Of Workload And Salary On The Performance Of Employees At The Public Accounting Firm Kanaka Puradiredja, Suhartono - Maria Nameka Sari Sitanggang; Hotner Tampubolon; Jonni Siagian (Fundamental Management Journal, 2026)
Employee Performance is the level of success of an individual or team in carrying out the tasks that are their responsibility, based on previously determined indicators. There are various factors that may lead to a decrease in employee performance, such as the lack of good management of employee workload and salary. The main goal about quantitative study is to identify how workload and salary affect employee performance at KAP Kanaka Puradiredja, Suhartono, South Jakarta branch. By using a saturated sampling technique, 30 office employees were selected as research samples. A Likert scale of 1 to 5 is included in the questionnaire used for data collection. In conducting descriptive analysis supported by Excel and SPSS software version 26.0. With the workload variable as (X1) having a significant level of 0,043 < 0,05, which indicates the result of the variable (X1) is significant. The t-count value of 2,05, t-count < t-table (2,128 > 2,052), suggests that the workload variable has a significant effect on employee performance at KAP Kanaka Puradiredja, Suhartono, South Jakarta branch. The outcome of the influence of the salary variable (X2) indicates a significant effect on employee performance at KAP Kanaka Puradiredja, Suhartono, South Jakarta branch, namely 0,001 > 0,05. The t-table value of 2,052 indicates that t-count > t-table (3,725 > 2,052). The simultaneous test produces the resulting F-statistic of 16,165, then the F-table value of 3,35. With the meaning that workload and salary significantly affect employee performance is significantly influenced, as indicated by a p-value of 0,000 (less than 0,05) and an F-statistic exceeding the critical value (16,165 > 3,35). Keywords: Workload, salary, employee performance.